Predictors of depressive symptoms in older adults living in care homes in Thailand - Tosangwarn, Suhathai; Clissett, Philip; Blake, Holly (Elsevier, 2018)
Background: Thai culture traditionally abhors elders living in care homes due to the belief that this represents a dereliction of filial piety by their children, thus care homes are stigmatized as the domain of poor older adults with no family. This may impact negatively on psychological wellbeing of residents, although little is known about the key factors influencing depressive symptoms. Therefore, this study explores factors associated with depressive symptoms, internalised stigma, self-esteem, social support and coping strategies among older adults residing in care homes in Thailand.